Sol-Gel Thin Film Processing for Integrated Waveguide Sensors - Alberti, Sebastián; Jágerská, Jana (Frontiers in Materials, 2021)
Integrated opto-chemical sensors present great advantages in comparison to the current lab equipment. They bring portability, reduced costs, facilitate in situ measurements, as well as largely reduced sample volumes. In this quest, standard processing protocols over established materials, such as silicon nitride, silicon, silicon dioxide, titanium oxide, and even a wide variety of polymers have so far been the key towards on chip devices. However, if very specific materials in terms of composition and tailored properties are required, the deposition via a solution represents a viable alternative. In this review, we highlight the role of sol-gel chemistry and top-down processing of sol-gel thin film layers in the design of waveguide-based optical sensors. In particular, we stress the advantages of porous sol-gel based materials as a new approach to increase sensitivity and selectivity, first when used as claddings, and, more recently, as waveguides with enhanced light–analyte interaction. We finally discuss the future perspectives of such devices to increase specificity in complex matrices, which is of utmost importance for bio-sensing.